Exposure to emotionally arousing, contamination-relevant pictorial stimuli interferes with response inhibition: Implication for obsessive–compulsive disorder - Adams, Thomas G. (J Obsessive Compuls Relat Disord, 2015)
Multiple emotional processes are implicated in the pathogenesis of obsessions and compulsions and individuals diagnosed with obsessive-compulsive disorder (OCD) have reliably shown deficits in response inhibition. Little research has tested how emotional processes might interact with cognitive control in the context of OCD. High contamination obsessive-compulsive (OC) and low contamination-OC participants completed an emotional go/no-go task to measure the interfering effects contamination-threat images relative to neutral images on action restraint (errors of commission). Results revealed that high contamination-OC participants committed marginally more commission errors (11.04%) than low contamination-OC participants (10.30%) on neutral no-go trials, but this effect was not significant (p > .05). All participants committed significantly more errors of commission on contamination-threat trails relative to neutral no-go trials, p < .01, but the interfering effects of contamination-threat images was significantly larger (p = .05) for high-contamination-OC participants. Errors of commission almost doubled for high contamination-OC participants on contamination-threat no-go trials (20.78%), compared to a more modest increase for low contamination-OC participants (14.80%). These findings suggest that individuals with elevated symptoms of OCD may have significantly more difficulty inhibiting their actions when processing disorder relevant or emotionally arousing information. This observation has implications for the pathogenesis of obsessions and compulsions.